2022
DOI: 10.1002/pbc.29927
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in children and adolescents with sickle cell disease after nonmyeloablative hematopoietic cell transplantation

Abstract: Background: Pulmonary complications are common in sickle cell disease (SCD). The use of standard myeloablative conditioning regimens may increase the risk of lung injury. We report serial pulmonary function testing (PFT) outcomes in children with SCD who underwent a matched-sibling donor hematopoietic cell transplantation (HCT) using nonmyeloablative (NMA) protocol.Methods: This is a retrospective chart review describing pulmonary outcomes in pediatric patients post HCT. The conditioning regimen consisted of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Like previous studies, we showed prolonged stability of lung function in most patients who underwent HSCT and very few pulmonary complications, with only one case of acute pulmonary GVHD. 4 In our cohort, the most frequent ventilatory defect in the posttransplant period was RVD, with an estimated prevalence of 24%. This prevalence probably varies with age and has been reported from 20% to 30% in similar studies.…”
mentioning
confidence: 67%
“…Like previous studies, we showed prolonged stability of lung function in most patients who underwent HSCT and very few pulmonary complications, with only one case of acute pulmonary GVHD. 4 In our cohort, the most frequent ventilatory defect in the posttransplant period was RVD, with an estimated prevalence of 24%. This prevalence probably varies with age and has been reported from 20% to 30% in similar studies.…”
mentioning
confidence: 67%
“…After reviewing the full‐text articles, another five studies were excluded based on study design (two because of missing outcome measure, one because of limited follow‐up, one was a literature review, and one because of different patient population). Finally, 34 studies were eligible for inclusion 8,18–50 . All 34 studies were used for the qualitative synthesis, of which 17 studies were also used in the meta‐analyses comparing organ function before and after HSCT.…”
Section: Resultsmentioning
confidence: 99%
“…In the meta‐analyses, there was no significant difference in FEV1 (SMD 0.08, p = .49), FVC (SMD 0.13, p = .35), or DLCO (SMD 0.95, p = .30) after HSCT as compared to before HSCT (Figure 2, Figure S1). The timepoint for the post‐HSCT assessment of pulmonary function was +2 years in three studies, 8,19,24 and after +3.2, +2.6, +2.4, and + 9 years in the other four studies 23,30,35,38 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations